The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2134/agronj15-0092
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and Quality of Winter Pea and Lentil in Alberta

Abstract: It is unknown if winter pea (Pisum sativum L.) and winter lentil (Lens culinaris Medik.) are feasible cropping options in Alberta. Field experiments were conducted at six locations in southern and central Alberta, Canada, between 2008 and 2012, to determine the adaptability of winter pea and lentil. Two winter pea cultivars, Specter and Windham, and one winter lentil cultivar, Morton, were seeded at three fall planting dates and three seeding rates. Spring cultivars were grown for comparison. In southern Alber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
1
8
1
Order By: Relevance
“…Please refer to Table 1 for environmental codes. study are in agreement with previous findings (Anthony et al 2012;Hood-Niefer et al 2012;Strydhorst et al 2015). A similar study showed that the protein concentration of dry pea ranged from 13.7% to 30.7% for samples collected from a different part of the world (Tzitzikas et al 2006).…”
Section: Protein Concentrationsupporting
confidence: 93%
See 2 more Smart Citations
“…Please refer to Table 1 for environmental codes. study are in agreement with previous findings (Anthony et al 2012;Hood-Niefer et al 2012;Strydhorst et al 2015). A similar study showed that the protein concentration of dry pea ranged from 13.7% to 30.7% for samples collected from a different part of the world (Tzitzikas et al 2006).…”
Section: Protein Concentrationsupporting
confidence: 93%
“…In contrast with starch concentration, considering the mean ash concentration for each location, a positive correlation was observed between ash concentration and the elevation of the testing locations. The mean ash concentrations reported in this study are generally less (only ranged up to 27.7 g kg −1 ) than the results reported by Strydhorst et al (2015) that ranged up to 34.5 g kg −1 for different cultivars and locations. These variations in ash concentration could be attributed to the differences in environments and genotypes used in the two studies.…”
Section: Ash Concentrationcontrasting
confidence: 86%
See 1 more Smart Citation
“…Variable contents of RS among different genotypes of rice (Chiu and Stewart, 2012) and wheat (Hazard et al, 2012) have been reported. Strydhorst et al (2015) found winter pea (cultivar Windham) had lower starch but higher resistant starch and protein than spring pea cultivars. However, research is needed regarding the variation of RS and protein among dry pea cultivars growing in different environments.…”
mentioning
confidence: 94%
“…Chen et al (2006) found that WP cultivars did not have a yield advantage over spring pea in central and south-central Montana. Similarly Strydhorst et al (2015) recommended that farmers consider WP over spring pea only in the southernmost locations in Alberta. Although edible dry pea was harvested on 206,000 ha in Montana in 2016(NASS, 2017 only about one percent of this was WP (P.R.…”
Section: Introductionmentioning
confidence: 99%